2020
DOI: 10.1103/physrevb.101.235205
|View full text |Cite
|
Sign up to set email alerts
|

Valley polarization investigation of GeS under high pressure

Abstract: GeS and its analog compounds exhibit unique properties that combine some of the most desired features of other two-dimensional compounds, such as transition-metal dichalcogenides and graphene. These include high electron mobilities or valley physics that result in strong optical and electronic anisotropy. Here, we present an experimental and theoretical study of the electronic band structure of GeS at high hydrostatic pressures. Polarization-resolved high-pressure photoreflectance measurements allow us to extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 68 publications
7
14
0
Order By: Relevance
“…It is seen that both the emission and absorption signals of the X transitions are linearly polarized along the same direction (167 • and 170 • , respectively). The result confirms directly the same origin of the X feature apparent in both the PL and RC spectra, as previously reported independently for the emission [12], photoreflectance [16],…”
Section: Optical Propertiessupporting
confidence: 91%
See 2 more Smart Citations
“…It is seen that both the emission and absorption signals of the X transitions are linearly polarized along the same direction (167 • and 170 • , respectively). The result confirms directly the same origin of the X feature apparent in both the PL and RC spectra, as previously reported independently for the emission [12], photoreflectance [16],…”
Section: Optical Propertiessupporting
confidence: 91%
“…We found that the low-temperature (T = 5 K) optical band-gap absorption is governed by a single resonance related to the neutral exciton, while the corresponding emission is dominated by disorder/impurity-and/or phonon-assisted recombination processes. Moreover, both the RC and PL spectra are found to be linearly polarized along the armchair direction of the crystal, which is consistent with previous works [12,16,17]. The measured RS spectra as a function of temperature from 5 to 300 K are composed of six Raman peaks, the energies and symmetries of which are in agreement with phonon dispersion calculated using Density Functional Theory (DFT).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is seen that both the emission and absorption signals of the X transitions are linearly polarized along the same direction (167 o and 170 o , respectively). The result confirms directly the same origin of the X feature apparent in both the PL and RC spectra, as previously reported independently for the emission 18 , photoreflectance 19 or absorption 20 . Moreover, according to Ref.…”
Section: B Optical Propertiessupporting
confidence: 91%
“…Recent works testing different DFT methods against experimentally determined HP optical, vibrational and structural properties of TMDCs have concluded that the widely employed LDA functional is too simplistic. Therefore, more advanced methods including the exchange-correlation functional in the generalized gradient approximation (GGA) with vdW corrections such as Grimme's D2 or D3 [30], Tkachenko-Scheffler [31] or meta-GGA SCAN functional [32] with rVV10 vdW functional [33], better predict the structural properties of layered materials [34,35]. In the present work we rely on the Perdew-Burke-Ernzerhof (PBE) parametrization [36] and D3 vdW correction, which has been shown to provide very good results for the HP behavior of 1T-TMDCs [34].…”
Section: First-principles Calculationsmentioning
confidence: 99%